2004
DOI: 10.1097/01.ju.0000141298.06350.4c
|View full text |Cite
|
Sign up to set email alerts
|

Face, Content and Construct Validity of the University of Washington Virtual Reality Transurethral Prostate Resection Trainer

Abstract: We established the face, content and construct validity for version 1.0 of the University of Washington TURP trainer to simulate the skills necessary to perform TURP. A predictive validity study showing a translation of skills from the virtual environment to the operating room will complete the validation of this model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 15 publications
2
43
0
1
Order By: Relevance
“…[14][15][16] Additionally, the field of urology has recognized the importance of simulation in training for other surgical techniques. [17][18][19][20][21] With regard to technical surgical training for laparoscopic and robotic surgery, most staff at academic centers would agree that they cringe at the thought of a novice trainee first undertaking particular surgical skills on an anesthetized patient with whom only the staff surgeon has made a connection, not to mention the relationship with the family and loved ones. For minimally invasive surgery, there are inanimate modes (box trainers) that can be helpful to trainees.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] Additionally, the field of urology has recognized the importance of simulation in training for other surgical techniques. [17][18][19][20][21] With regard to technical surgical training for laparoscopic and robotic surgery, most staff at academic centers would agree that they cringe at the thought of a novice trainee first undertaking particular surgical skills on an anesthetized patient with whom only the staff surgeon has made a connection, not to mention the relationship with the family and loved ones. For minimally invasive surgery, there are inanimate modes (box trainers) that can be helpful to trainees.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopy and endoscopy have proven to be ideally suited for the use of virtual-reality models for simulation training. This approach allows for virtual mentorship, task deconstruction, and the ability to study dynamic comprehensive surgical metrics [1,2]. With the introduction of the surgical robot in 2001, an additional laparoscopic technological adjunct became available that arguably requires a shorter learning curve for attaining appropriate surgical skills.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have been conducted throughout the development of the University of Washington VR TURP simulator (Medical Education Technologies Inc, Sarasota, FL. 6,[9][10][11][12][13] These studies demonstrated a strong construct and discriminate validity, realistic blood loss simulation, and improved outcomes with task deconstructions versus full task-training. A similar approach was taken in the development of the resident exposure to transurethral surgical options for BPH GreenLight VR simulator.…”
Section: Discussionmentioning
confidence: 99%